Effectiveness of maintanance system at palm oil mill - Mohamad Azwani, Londing (2016)
Effectiveness maintenance implementation can improve a company’s profitability for increase the productivity, facilitate cost reductions identify new business opportunities and help develop market competitiveness. This study aims to identify the type of maintenance system implemented at palm oil mill and to analyze the effectiveness of maintenance system implemented in their mill. To achieve this objectives, three palm oil mills in Gua Musang, Kelantan were chosen to be studied. The interview session was conducted between manager and assistant manager in operation department. On overall, interview result showed that the types of maintenance system implemented at palm oil mill are the PV40, corrective maintenance, continuous maintenance and productive maintenance. Findings showed that the positive result produce from implemented maintenance system are different for each mill. The improvement occur in production quality, percentage of Crude Palm Oil (CPO) extraction and number processed BTS.